Intra-Renal Angiotensin Levels Are Increased in High-Fructose Fed Rats in the Extracorporeal Renal Perfusion Model - Yokota, Rodrigo; Ronchi, Fernanda Aparecida; Fernandes, Fernanda Barrinha; Jara, Zaira Palomino; Rosa, Rodolfo Mattar; Leite, Ana Paula de Oliveira; Fiorino, Patricia; Farah, Vera; Nascimento, Nilberto Robson Falcão do; Fonteles, Manassés C.; Casarini, Dulce Elena (Frontiers in Physiology, 2018)
Overconsumption of fructose leads to metabolic syndrome as a result of hypertension, insulin resistance, and hyperlipidemia. In this study, the renal function of animals submitted to high fructose intake was analyzed from weaning to adulthood using in-vivo and ex-vivo methods, being compared with a normal control group. We investigated in ex-vivo model of the role of the renin angiotensin system (RAS) in the kidney. The use of perfused kidney from animals submitted to 8-week fructose treatment showed that high fructose intake caused metabolic and cardiovascular alterations that were consistent with other studies. Moreover, the isolated perfused kidneys obtained from rats under high fructose diet showed a 33% increase in renal perfusion pressure throughout the experimental period due to increased renal vascular resistance and a progressive fall in the glomerular filtration rate, which reached a maximum of 64% decrease. Analysis of RAS peptides in the high fructose group showed a three-fold increase in the renal concentrations of angiotensin I and a two-fold increase in angiotensin II levels, whereas no change in angiotensin 1-7 was observed when compared with the control animals. We detected a decrease in ACE activity in renal tissues, but high concentrations of angiotensin II. These observations suggest that alternative pathways for angiotensin II production exist in this model. Chymase, tonin, and cathepsin are possible enzymes responsible for the observed angiotensin II increase. The increased production of the intrinsic renal angiotensin I and II in high-fructose fed rats led to adaptive renal function changes that are probably associated with both increased blood pressure in these animals and kidney damage associated with this model.